Knockdown of ENTPD5 inhibits tumor metastasis and growth via regulating the GRP78/p-eIF-2α/CHOP pathway in serous ovarian cancer - Xueping Chen; Zhiqiang Zha; Yu Wang; Yun Chen; Menglan Pang; Liping Huang; Yao Chen (BMC, 2022)
Abstract Background Dysregulation of Ectonucleoside Triphospahate Diphosphohydrolase 5 (ENTPD5) in tumors might be associated with tumor progression, while the role of ENTPD5 in the growth and metastasis of serous ovarian cancer (SOC) is still unclear. Methods ENTPD5 expression patterns in ovarian cancer tissues were analyzed by qRT-PCR and immunohistochemistry assay (IHC). Two SOC cell lines, SKOV3 and OVCAR8, were stably transfected with lentivirus to build knockdown and overexpression cell lines. Clone formation assay, collagen gel droplet culture technology, wound healing assay and flow cytometry were used to assess the migration and growth traits of SOC cells. Expression levels of ENTPD5, glucose regulated protein 78 (GRP78), eukaryotic translation initiation factor 2 alpha (eIF-2α), phosphorylated -eIF-2α and, C/EBP homologous protein (CHOP) in SOC cells were detected by Western blot. Results Compared to fallopian tube tissues, the expression of ENTPD5 was significantly higher in tumor tissues obtained from SOC patients, and positively correlated with clinical stage and metastasis. ENTPD5 knockdown robustly inhibited cell proliferation, migration, whereas ENTPD5 overexpression elicited the opposite effect on SOC cells. ENTPD5 knockdown arrested cell cycle in G0/G1 phase and increased apoptosis. Importantly, ENTPD5 knockdown was associated with significantly decreased protein levels for GRP78, CHOP, and p-eIF-2α, suggesting possible involvement of ENTPD5 in endoplasmic reticulum stress (ERS). Conclusions Our study demonstrates that ENTPD5 knockdown inhibited SOC cell proliferation, migration and restrained the activation of the GRP78/p-eIF-2α/CHOP pathway, which provides a potentially effective therapeutic target for the treatment of SOC.